QUALITY OF NURSING WORK LIFE DENGAN BURNOUT SYNDROME DI RSUD dr. R. KOESMA TUBAN - Tiara Putri Ryandini; Mokhamad Nurhadi (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Burnout Syndrome is a psychologically severe labor condition that is at risk of disrupting the quality of work productivity in providing services. The purpose of this study was to determine the relationship between the Quality of Nursing Work Life and Burnout Syndrome at RSUD dr. R. Koesma Tuban (Bougenville Room, Lotus and Orchids).This study uses a correlational analytical research design with cross-sectional. The population used were all nurses in the inpatient room at RSUD dr. R. Koesma Tuban totaled 47 nurses using simple random sampling. This data collection uses a questionnaire with spearmen rank analysis. Statistical test results show the value of sig. (2-tailed) of 0.01, because the value of sig. (2-tailed) of 0.05 means that H1 is accepted so that there is a relationship between Quality Of Nursing Work Life and Burnout Syndrome at RSUD dr. R. Koesma Tuban (Room Bougenville, Lotus, And Orchid). This study concludes that there is a relationship between the Quality of Nursing Work Life and Burnout Syndrome in dr. R. Koesma Tuban (Room Bougenville, Lotus, And Orchid). Respondents are expected to know the importance of the quality of work life of nurses to minimize the incidence of burnout syndrome.